Laboratory study of bioaerosols: Traditional test systems, modern approaches, and environmental control. Issue 5 (3rd May 2020) - Santarpia, Joshua L.; Ratnesar-Shumate, Shanna; Haddrell, Allen
Abstract: Biological aerosol particles have been studied in the laboratory for many decades to understand their roles in human health and disease and in environmental processes. These studies have used a variety of instrumentation under varying conditions. This review covers the most common types of bioaerosol chambers (e.g., static, flow-through and rotating drum), the study of biological particles captured on spider's webs, and single particle levitation systems (optical, acoustic and electrodynamic). It also discusses the variety of ways the study environment (temperature, humidity, light and trace gas) may impact biological particles through modification of both biological properties, such as proteins, DNA, and viability, and the physical properties such as size and fluorescence that are relied upon for measurement. The result is a broad look at the many ways biological particles can be studied in the laboratory and the many factors that past studies have determined impact the properties of bioaerosols.